Completing Medication with Sufism: A Holistic Approach to Trauma Recovery - Masykur, Zein Muchamad; Ismatullah, A.M. (Jurnal Studi Agama dan Masyarakat, 2024)
The experience of psychological trauma can be profoundly distressing, significantly impacting an individual’s well-being, which makes it essential to explore effective Sufi methods in trauma therapy. The study aimed to analyze active Sufi methods in trauma therapy and their contributions to modern psychotherapy. This research was conducted through an in-depth review of published literature concerning applying Sufi methods in trauma therapy. The data sources were articles, journals, books, and other relevant materials. Data analysis was carried out thematically to identify and explore the key themes and concepts emerging from the literature. The study demonstrates that many Sufi practices—such as zikir, muraqabah, and khalwah—are imbued with immense potential for trauma therapy. Zikir leads to calmness and self-reflection, muraqabah enhances self-awareness and spiritual connection, and khalwah provides profound introspection and a sense of peace. This research concludes that Sufi practices can be integratively employed to facilitate trauma therapy, addressing somatic, emotional, and spiritual dimensions comprehensively. What is offered here is the potential integration of Sufi practices into trauma therapy frameworks to provide a more holistic and culturally relevant healing pathway for those coping with trauma.